Optimization of Fermentation Condition for Hydrolytic Enzyme Production by Endophytic Bacteria from Kleinhovia hospita L. - Armini Syamsidi; Ni Gusti Ayu Puja Erawati; Angelika Brigita Ali; Indriati; Aurelia Amarilis; Wa Ode Sitti Musnina (JSFK (Jurnal Sains Farmasi & Klinis), 2026)
Kleinhovia hospita L. is a tropical Indonesian medicinal plant that hosts endophytic bacteria capable of producing hydrolytic enzyme proteins through fermentation. Enzyme production is influenced by fermentation pH and temperature, which affect enzymatic reactions, microbial growth, and enzyme synthesis. This study evaluated the activity of hydrolytic enzymes produced by endophytic bacteria isolated from K. hospita L. and examined were the effects of fermentation pH and temperature at pH 5, 7, and 10 and temperatures of 28, 34, and 40 °C. Enzyme activity was analyzed using the well diffusion method, and enzyme protein content was measured using the biuret method with BSA as a standard. The highest protein concentrations were observed at pH 5 in isolate KHD1 (507.5 mg/mL), pH 7 in isolate KHD2 (560 mg/mL), and pH 10 in isolate KHB1 (607.5 mg/mL). All isolates showed amylase activity, with the highest clear zone diameter recorded in isolate KHD2 (12.79 ± 0.24 mm). Pectinase and esterase activities were highest in isolates KHD1 and KHB1, respectively, while isolate KHA1 exhibited the highest lipase, cellulase, and protease activities. Fermentation pH and temperature significantly affected hydrolytic enzyme protein activity, indicating that endophytic bacteria from K. hospita L. are promising sources of hydrolytic enzymes.